Analysis of effectiveness and safety of cisatracurium infusion during laparoscopic abdominal surgery - Hong, Zhe; Lin, Xintong; Jin, Weifang (Frontiers in Surgery, 2025)
ObjectiveTo explore the efficacy and safety of different infusion modes of cisatracurium in laparoscopic abdominal surgery.MethodsIn this randomized controlled trial, 90 patients undergoing elective laparoscopic abdominal surgery at Shanghai Civil Aviation Hospital (2019–2020) were allocated to either continuous (n = 45) or intermittent (n = 45) cisatracurium infusion groups. Operation time, dosage of cisatracurium, time of onset, lack of muscle relaxant occurrences, extubation time, recovery index (TOF T1 recovery from 25% to 75%), TOF70% (drug withdrawal to TOF recovery time for 70%), TOF90% (drug withdrawal to TOF recovery time for 90%), mean arterial pressure and heart rate during anesthesia and induction, and occurrence of adverse reactions were compared between the two groups.ResultsWhile onset time (P = 0.102) and operation duration (P = 0.946) were comparable between groups, the continuous infusion group demonstrated significant advantages: fewer inadequate relaxation episodes (P = 0.003), lower total cisatracurium requirements (P < 0.001), and faster recovery (recovery index, TOF70%, and TOF90%; all P < 0.001). There was no significant difference in mean arterial pressure and heart rate during the anesthesia and induction between the two groups (P = 0.314, P = 0.462 and P = 0.205, P = 0.521). Meanwhile, extubation times (P = 0.095) and adverse event rates (P = 0.214) showed no significant differences.ConclusionsCompared with intermittent infusion, continuous infusion of cisatracurium provides better muscle relaxation effect with reduced cisatracurium consumption and faster recovery, without increasing the risk of residual muscle relaxation or adverse reactions in this study, suggesting a favorable safety in laparoscopic abdominal surgery.